Prevalence and seroconversion of hepatitis C among hemodialysis patients in Assiut governorate, Egypt - Kerollos Motwade N. Kerollos; Hussein Ahmed El-Ameen; Lobna Abd El Wahed; Nashwa Mostafa A. Azoz (SpringerOpen, 2020)
Abstract Background The prevalence of hepatitis C (HCV) infection among the patients on hemodialysis (HD) varies from country to country and from one center to another in the same country. Despite the existence of guidelines for the infection control program, Egypt is one of the countries with high HCV prevalence. In Egypt, the prevalence of HCV among hemodialysis patients in 2015 survey was 50.7%. This study aimed to evaluate the prevalence and seroconversion rate of hepatitis C infection and the risk factors for seroconversion in our community hemodialysis units. Results The prevalence of HCV was 34.8% among hemodialysis patients. The seroconversion rate was 13.2%. The positive history of blood transfusion and the frequency of blood transfusion, in addition to the handling by medical staff to equipment and blood products and the number of inserted temporary dialysis catheters, were found to be significant risk factors for seroconversion. Conclusion We concluded that there is a high prevalence of HCV infection in the dialysis units of our community and a relatively high seroconversion rate among hemodialysis patients.